2004
DOI: 10.1111/j.1365-2141.2004.05059.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual consistency of the activated protein C resistance phenotype

Abstract: Summary Resistance to activated protein C (APC) has been demonstrated to be a risk factor for venous thromboembolism, but it is not known whether this phenotype is consistent over time. We reinvestigated 2580 subjects from the Vicenza Thrombophilia and Atherosclerosis (VITA) Project to evaluate the prevalence of a consistent APC resistance phenotype in the population. Among the 433 subjects with an APC resistance at first visit, the phenotype was confirmed in all the 74 factor V (FV) Leiden carriers and in 124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Soon after the discovery of APC resistance it was observed that not all individuals with a poor APC‐response carry the FV Leiden mutation, which suggested the existence of additional causes of APC resistance [4,34]. APC resistance in the absence of FV Leiden is in fact very prevalent in the general population (10–15% of individuals, as determined with the aPTT‐based test [47,48]) and is also associated with an increased risk of venous thrombosis [8–10]. The underlying causes may be genetic or acquired and depend on the APC resistance assay used.…”
Section: Fvleiden‐independent Apc Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Soon after the discovery of APC resistance it was observed that not all individuals with a poor APC‐response carry the FV Leiden mutation, which suggested the existence of additional causes of APC resistance [4,34]. APC resistance in the absence of FV Leiden is in fact very prevalent in the general population (10–15% of individuals, as determined with the aPTT‐based test [47,48]) and is also associated with an increased risk of venous thrombosis [8–10]. The underlying causes may be genetic or acquired and depend on the APC resistance assay used.…”
Section: Fvleiden‐independent Apc Resistancementioning
confidence: 99%
“…Genetic factors other than FV Leiden also importantly contribute to plasma APC resistance, as illustrated by a large population survey indicating that ∼5% of individuals who do not carry FV Leiden are APC‐resistant at repeated testing [47]. The heritability (i.e.…”
Section: Fvleiden‐independent Apc Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Research showed that in 10-15% of individuals who are APC resistant (as determined via an APTT-based assay), the FVLeiden mutation is not present (Taralunga et al, 2004;Tosetto et al, 2004). This implies that besides FVLeiden, other factors exist that may modify the outcome of an APC resistance assay.…”
Section: Modifiers Of the Apc Resistance Phenotypementioning
confidence: 99%
“…In the APTT-based APC resistance assays other factors besides OC use and pregnancy were found to be prevalent among cases on non-FVLeiden APC resistance. These include high FVIII levels, elevated prothrombin levels, malignancy and the presence of lupus anticoagulants (Henkens et al, 1995;Cumming et al, 1995;Laffan & Manning, 1996;Aznar et al, 1997;Tosetto et al, 1997;de Visser et al, 1999;Castaman et al, 2001;Tosetto et al, 2004;Taralunga et al, 2004;Sarig et al, 2005). Several allelic variants of the FV gene have been described that contribute to the APC resistance phenotype and to venous thrombosis.…”
Section: Modifiers Of the Apc Resistance Phenotypementioning
confidence: 99%